Genome-Wide Comprehensive Analysis of the SABATH Gene Family in Arabidopsis and Rice. (July 2019) - Wang, Bin; Li, Min; Yuan, Yijun; Liu, Shaofang
Low molecular weight metabolites are important plant hormones and signaling molecules, and play an important part among the processes of plant development. Their activities may also be affected by the chemical modifications of methylation performed by SABATH. In this study, a total of 24 and 21 SABATH genes in Arabidopsis and rice, respectively, were identified and taken a comprehensive study. Phylogenetic analysis showed that AtSABATH and OsSABATH genes could be classified into 4 major groups and 6 subgroups. Gene expansion analysis showed that the main expansion mechanism of SABATH gene family in Arabidopsis and rice was tandem duplication and segmental duplication. The ratios of nonsynonymous (Ka) and synonymous (Ks) substitution rates of 12 pairs paralogous of AtSABATH and OsSABATH genes indicated that the SABATH gene family in Arabidopsis and rice had gone through purifying selection. Positive selection analysis with site models and branch-site models revealed that AtSABATH and OsSABATH genes had undergone selective pressure for adaptive evolution. Motif analysis showed that certain motifs only existed in specific subgroups or species, which indicated that the SABATH proteins of Arabidopsis and rice appear divergence in different species and subgroups. Functional divergence analysis also suggested that the AtSABATH and OsSABATH subgroup genes had functional differences, and the positive selection sites which contributed to functional divergence among subgroups were detected. These results provide insights into functional conservation and diversification of SABATH gene family, and are useful information for further elucidating SABATH gene family functions.